THE DEVELOPMENT OF REGIONAL ECONOMY IN TIMES OF CRISIS - E. Frantseva-Kostenko (Вестник университета, 2019)
Тhe article is devoted to the topical subject of a modern economy-development of regional economy in crisis, because of the need to determine the competitive status of the region (municipality), identification of factors of instability for further dynamic socio-economic development of the territory. The author of the article proposes an indicative list of factors for assessing the volatility of the regional economy in the context of a systemic crisis.